(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify (evaluating the performance of primary school principals according to their competencies from the point of view of their assistants) and based on that, a goal was formulated to identify: evaluating the performance of primary school principals according to their competencies from the point of view of their assistants, and knowing individual differences in terms of gender, and to achieve the research objectives. The researcher prepared the competencies tool to evaluate performance, as it consisted of (49) items in the form The final analysis was divided into seven areas. After that, the researcher applied the research tool to the sample of (229) primary school assistants in Rusafa Third Education, with (128) males and (101) females, chosen from the basic research sample of (563). (41%) individuals. After completing the application of the research tool on the sample, the data was transcribed and analyzed using a program. Computer (SPSS) and statistical methods were used (arithmetic mean, standard deviation, hypothetical mean, Cronbach, one-sample t-test, Pearson correlation coefficient, t-value) and the research reached the following results that primary school principals have competencies in performing work.